Has the Nature of Crises Changed? : A Quarter Century of Currency Crises in Argentina - Choueiri, Nada (IMF Working Papers; Working Paper, 1999)
The recent turmoil in currency markets in Asia, Europe, and Latin America has given a new impetus to the literature on currency crises. The literature originally linked currency crises to deteriorating economic fundamentals, but has more recently focused on self-fulfilling expectations and contagion. To assess the changing roles of domestic and external market fundamentals and contagion, this paper examines seven major currency crises in Argentina. It finds that while crises in the 1970s and 1980s were driven mainly by monetary and fiscal policies at home and abroad, contagion played an important role in the 1990s.